Femtosecond Laser vs. Conventional Phacoemulsification: Long-Term Posterior Capsule Opacification - Jamal Hussain, Nawab Ali Khan, Abshar Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Posterior capsule opacification (PCO) is the most common long-term complication after cataract surgery and may lead to decreased visual acuity requiring Nd:YAG laser capsulotomy. Advances in surgical techniques such as femtosecond laser–assisted cataract surgery aim to improve surgical precision and potentially reduce postoperative complications. Objective: To compare the long-term incidence of posterior capsule opacification between femtosecond laser–assisted cataract surgery and conventional phacoemulsification. Methodology: This was a hospital-based analytical cross-sectional study conducted at Swat Medical Complex Teaching Hospital from March 2021 to march 2022 including 235 patients undergoing cataract surgery. Results: The mean age of patients was 63.8 ± 8.7 years with nearly equal gender distribution. Capsulotomy diameter was more consistent in the femtosecond group (5.01 ± 0.06 mm) compared with the conventional group (5.19 ± 0.21 mm). Ultrasound energy (5.9 ± 2.3% vs 9.8 ± 3.1%) and effective phaco time (27.4 ± 7.8 vs 39.6 ± 9.5 seconds) were significantly lower in the femtosecond group. Posterior capsule opacification occurred in 11.9% of patients in the femtosecond group compared with 23.9% in the conventional group. Nd:YAG capsulotomy was required in 7.6% of patients in the femtosecond group and 17.1% in the conventional group. Postoperative visual acuity was slightly better in the femtosecond group (0.07 ± 0.05 logMAR) compared with the conventional group (0.10 ± 0.07 logMAR). Conclusion: Femtosecond laser–assisted cataract surgery demonstrated improved surgical precision, reduced ultrasound energy use, and lower incidence of posterior capsule opacification compared with conventional phacoemulsification. Keywords: Cataract surgery, Femtosecond laser, Phacoemulsification, Posterior capsule opacification, Nd:YAG capsulotomy, Visual outcomes.